Simulation analysis of double-sided lc network for wireless capacitive transcutaneous energy transfer - Yusop, Yusmarnita; Qi, Cheok Yan; Saat, Shakir; Husin, Huzaimah; Shaktivel, R. (2023)
This paper presents the design and simulation analysis of load and coupling variations for a current Wireless Power Transfer (WPT) technique, known as Capacitive Power Transfer (CPT). Due to its strength, CPT becomes an effective and essential alternative to conservative technique, which is Inductive Power Transfer (IPT). It can compete IPT in industrial demand since it has a small number of component usage, uncomplicated topology, increases electromagnetic interference (EMI) shielding performance and robust to surrounding metallic elements. Class E power amplifier with the presence of LC network circuit is applied in this work as a high frequency ac power source since it has the ability to perform dc-to-ac inversion efficiently. It supports the CPT system to attain a maximum power transmission. MATLAB software is used to design and simulate the proposed CPT circuit; and the analysis is made up from the results. This proposed system able to generate 1W of output power by maintaining up to 98% efficiency at 6.78MHz operating frequency for Biomedical Implantable Device application. The analysis of load variation is in the range of 50Ω until 1kΩ; meanwhile for coupling variation is between 1mm to 15mm.